THE INFLUENCE OF MARKERS IN THE DIFFERENTIATION PROCESS OF STEM CELLS INTO ENDOTHELIAL CELLS TO SUPPORT TREATMENT TESTING EXPERIMENTS - Nurdiyati, Nanis (Journal of Stem Cell Research and Tissue Engineering, 2024)
Research on stem cells, particularly their differentiation into endothelial cells, is highly significant in the field of biomedical science and regenerative therapy. Endothelial cells are crucial for blood vessel formation, wound healing, tissue regeneration, and the treatment of degenerative diseases. Human pluripotent stem cells can differentiate into various cell types, making them valuable for repairing or replacing damaged tissue. This study reviews the role of markers in distinguishing human stem cells into endothelial cells. A comprehensive literature search was conducted, and out of 428 screened articles, only 4 met the inclusion criteria. SOXF proteins were analyzed using scRNA-seq analysis, focusing on their role in enhancing stem cell differentiation. SOX17 was found to significantly increase the percentage of cells expressing CD34+ and Vascular Endothelial Cadherin (VEC), consistent with its known role in endoderm differentiation and endothelial cell specification. SOX17 can override pluripotency signals in human stem cells, triggering their differentiation into endothelial cells. Overexpression of SOX17 in human stem cells resulted in cells with endothelial characteristics, and combining SOX17 with FGF2 enhanced this effect, resulting in more than 90% of cells expressing endothelial stem cell markers (CD34+, VEC+, CD31+). SOXF was applied to prompt stem cell differentiation, with only SOX17 demonstrating notable effectiveness.